Impacto de la reforma laboral de la ley 789 de 2002 en la política pública de disminución de desempleo en Colombia (2010)
The present investigation has as end to carry out a study, to understand and to explain the labor reformation originated in the law 789 of December of 2002, 27 for which the national government adopts a series of measures that you/they have as fundamental objective that the unemployment index diminished. It is of vital importance that the right students know the impact that generated this law to some labor sectors, since the Government he/she thought of generating more employment but what was achieved is that the employment quality deteriorates, because the workers dedicate more time of work to obtain an inferior remuneration to which was possible to obtain with the previous legislation. The present investigation took this method, observing the causes and consequences that the law 789 of 2002 specified to the Colombian legislation to motivate to the decrease to the unemployment; it is of utility in the development of this work to observe the situation that was generated by this norm in labor matter and to be able to find a possible artificial solution. The conclusion that should stand out like part of the recent debate in the country, is that the apparent paradox of more growth economic and smaller employment according to the most recent data of the one DAMAGED, it is not unaware to the development pattern continued by the governments of the opening. The current situation one has come presenting in the country along this process and it has been recognized and diagnosed at least in the administrations of 1994 and 1998.